Cinnamon inhibits platelet function and improves cardiovascular system - Mahdieh Mehrpouri; Rafie Hamidpour; Mohsen Hamidpour (Institue of Medicinal Plants, ACECR, 2020)
Background: Cinnamon belongs to the Lauraceae family and is one of the most common spices that are used as traditional medicine in the world. The bark and leaf of cinnamon contain essential oils and derivatives including cinnamaldehyde, cinnamic acid and several other compounds such as polyphenols. Moreover, anti-inflammatory and lipid lowering properties of cinnamon has been proven. Objective: The goal of this review is to find out whether cinnamon extract was used as an anticoagulant and anti-aggregation properties for the platelets or not. Methods: Using the search engine tools such as PubMed and Scopus, the articles that were studied cinnamon and its effects on platelets function and cardiovascular disease were under reviewed. Results: This article presents a comprehensive analysis of cinnamon compounds and their effects on platelet function and cardiovascular disease. Conclusion: Taken together, data show that cinnamon extract can inhibit platelet function and as a complementary medicine were used in cardiovascular disorder.